Disseminated histoplasmosis: A comparative study between patients with acquired immunodeficiency syndrome and non-human immunodeficiency virus-infected individuals (2005)
ABSTRACT : We studied 52 patients with disseminated histoplasmosis, 30 with the acquired immunodeficiency syndrome (AIDS) (cohort 1) and 22 not co-infected with the human immunodeficiency virus (cohort 2). Demographic, clinical, laboratory, mycologic findings, as well as antifungal therapy and highly active antiretroviral (HAART), were analyzed. Skin lesions were significantly higher in cohort 1 than in cohort2(P 0.001). Anemia, leukopenia, and an elevated erythrocyte sedimentation rate were also more pronounced in cohort 1 than in cohort 2 (P < 0.001). Histoplasma capsulatum was isolated more often in cohort 1 than in cohort 2 (P < 0.05) patients, but antibodies to H.capsulatum were detected more frequently in cohort 2 than in cohort 1 (P < 0.05). Itraconazole treatment was less effective in cohort 1 than in cohort 2 (P 0.012). In cohort 1 patients, HAART improved response to antifungals when compared with individuals not given HAART (P 0.003), who exhibited higher mortality rates (P 0.025). Cohort 1 patients who were given dual antifungal and anti-retroviral therapies responded as well as the non-HIV patients in cohort 2, who were treated only with itraconazole. These results indicate the need to promote restoration of the immune system in patients with AIDS and histoplasmosis.